(untitled) (Research, Society and Development, 2022)
In the complex floodplain context, the riverside caboclo constitutes his home, which is delimited by the water regime. Related to the variations in the level of the rivers, some houses are periodically affected in lowland areas, the riverside dwellers seek different ways to adapt, among these forms, being Seasonal Mobility, since it presents greater environmental rationality. This study aimed to characterize the occupation of space and the housing situation of the Nossa Senhora das Graças community, in the Municipality of Manacapuru / AM. To carry out this study, primary data were used, collected from September to December 2020. They were recovered with the heads of households, through the application of semi-structured forms, defining the socioeconomic, housing and spatial aspects of the community. Spatial and structural adaptations were observed in the houses that adapt to seasonal changes related to rising water.